Medical-Surgical nursing : - Ignatavicius, Donna D. (Elsevier, 2016)
This edition continues the book’s trendsetting tradition with increased LGBTQ content and a new Care of Transgender Patients chapter. Cutting-edge coverage of the latest trends in nursing practice and nursing education prepares you not just for today’s nursing practice but also for tomorrow’s